Sphincter of Oddi dysfunction: an evidence-based review. (November 2013) - Rehman, Abdul; Affronti, John; Rao, Satish
Sphincter of Oddi dysfunction is a painful syndrome that presents as recurrent episodes of right upper quadrant biliary pain, or recurrent idiopathic pancreatitis. It is a disease process that has been a subject of controversy, in part because its natural history, disease course and treatment outcomes have not been clearly defined in large controlled studies with long-term follow-up. This review is aimed at clarifying the state-of-the-art with an evidence-based summary of the current diagnostic and therapeutic approaches and modalities for sphincter of Oddi dysfunction.